Lacan's Theory of Desire and Its Practical Value - Wang, Wengqiu; Jia, Yupeng (International Journal of Linguistics, 2021)
The word "desire" is one of the core terms in Lacan's psychoanalysis. As the famous saying of Lacan: "the desire of man is the desire of the Others", Lacan's theory of desire is based on Hegel - Koyev's theory of desire. By falsifying the subject, Lacan developed a unique theory of desire, that is, desire is the alienated subject, the fantasy formed in the pursuit of what Freud called the Das Ding which Lacan called the Objet petit A, and finally the fantasy constructs desire retrospectively. The study of Lacan's theory of desire helps to provide more sections for the study of contemporary social phenomena and social development.